2023
DOI: 10.23876/j.krcp.22.274
|View full text |Cite
|
Sign up to set email alerts
|

Shortening of primary cilia length is associated with urine concentration in the kidneys

Abstract: Background: The primary cilium, a microtubule-based cellular organelle present in certain kidney cells, functions as a mechano-sensor to monitor fluid flow in addition to various other biological functions. In kidneys, the primary cilia protrude into the tubular lumen and are directly exposed to pro-urine flow and components. However, their effects on urine concentration remain to be defined. Here, we investigated the association between primary cilia and urine concentration. Methods: Mice either had free acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…4), which also excludes the possibility of artifacts as urine osmolarity should be altered gradually in vivo. A recently published work further supports our in vitro findings and above-mentioned idea, as water deprivation causes shortening of renal primary cilia in vivo (Kong et al, 2023).…”
Section: Discussionsupporting
confidence: 91%
“…4), which also excludes the possibility of artifacts as urine osmolarity should be altered gradually in vivo. A recently published work further supports our in vitro findings and above-mentioned idea, as water deprivation causes shortening of renal primary cilia in vivo (Kong et al, 2023).…”
Section: Discussionsupporting
confidence: 91%
“…[3] For instance, leptin treatment increases the cilium length of hypothalamic neuronal cells; [4] insulin mediates negative feedback mechanisms that regulate cilium length during adipogenic differentiation; [5] and cilia on renal tubular epithelial cells are shortened upon water deprivation. [6] A recent study elegantly demonstrated that cilium length in the hypothalamus undergoes periodic changes, which are associated with circadian rhythms. [7] Dysregulation of cilium length causes multiple types of organ dysfunction, leading to a class of diseases called ciliopathies.…”
Section: Introductionmentioning
confidence: 99%
“…In the current issue of Kidney Research and Clinical Practice, Kong et al [6] reported an association between water balance and primary cilia length. As expected, they found that water deprivation enhanced urine concentration and 280 www.krcp-ksn.org Kidney Res Clin Pract 2023;42(3):279-281 aquaporin-2 (AQP2) in mice.…”
mentioning
confidence: 99%
“…In particular, acetylation is a characteristic of α-tubulin in the cilia, but not in the cytoplasm [1]. Acetylated α-tubulin was also used in the current study [6] as the standard marker of cilia.…”
mentioning
confidence: 99%
See 1 more Smart Citation